Adaptive Chebyshev Neural Network Control for Ventilator Model under the Complex Mine Environment. (27th August 2020) - Liu, Ranhui; Hu, Xinyan; Zhang, Chengyuan; Liu, Chuanxi
Abstract : Ventilator is important equipment for mines as it safeguards the lives under the shaft and ensures other equipment's proper functioning by providing fresh air. Therefore, how to effectively control the ventilator system becomes more significant. In order to acquire the commonly used model and control strategy for ventilator systems, a new universal ventilator model is established based on the blast capacity differential pressure in the ventilating duct and the ventilator motor model. Then, an adaptive Chebyshev neural network (ACNN) controller is proposed to effectively control the ventilator system where the unknown load torque and the unknown disturbance caused by the complex environment under the shaft are approximated by the Chebyshev neural network (CNN). Afterwards, an appropriate Lyapunov function candidate is designed to guarantee the stability of the proposed controller and the closed-loop ventilator system. Finally, the ACNN controller has been demonstrated to be effective in terms of validity and precision for the new proposed ventilator model through the simulations.